Serum and Urinary N-Terminal Pro-brain Natriuretic Peptides as Biomarkers for Bronchopulmonary Dysplasia of Preterm Neonates - Iliodromiti, Zoi; Christou, Evangelos; Vrachnis, Nikolaos; Sokou, Rozeta; Vrachnis, Dionysios; Mihopoulou, Georgia; Boutsikou, Theodora; Iacovidou, Nicoletta (Frontiers in Pediatrics, 2020)
Bronchopulmonary dysplasia (BPD) is a common cause of respiratory illness in preterm newborns with high morbidity and mortality rates. At present, there are no early prognostic biomarkers that can be used in clinical practice to predict the development of BPD. In this review, we critically appraise evidence regarding the use of serum N-terminal pro-brain natriuretic peptide (NTproBNP) levels as a biomarker for BPD in neonates. Furthermore, we summarize studies assessing the feasibility of urinary NTproBNP levels as a non-invasive method to predict BPD in preterm infants. Multiple studies reported a strong association between NTproBNP serum levels and the onset of BPD. For urinary NTproBNP little evidence exists in the literature, but the association with BPD also seems to be present. Given the promising data obtained by preliminary studies, further assessment of this biomarker in both serum and urine is warranted. Standardized reference values should be defined before conducting clinical studies.